Program and abstracts : September 6-9, 2003 : 3th International Posture symposium, Smolenice castle, Slovakia (Institute of Normal and Pathological Physiology Slovak Academy of Sciences, 2003)
A program and a collection of abstracts of works presented at a symposium that focused on posture and posture diseases. Intended for professional public.
Keywords: Musculoskeletal Diseases; postura těla; fyziologie; muskuloskeletální nemoci; Posture; Rehabilitation; rehabilitace